Decay of kaonium in a chiral approach - Klevansky, Sandra Pamela; Lemmer, Richard H. (Physics letters, 2011)
The decay of the K+K− hadronic atom kaonium is investigated non-perturbatively using meson-meson interaction amplitudes taken from leading order chiral perturbation theory in an approach adapted from that proposed by Oller and Oset (1997) [18]. The Kudryavtsev-Popov eigenvalue equation is solved numerically for the energy shift and decay width due to strong interactions in the 1s state. These calculations introduce a cutoff ∼1.4 GeV in O(4) momentum space that is necessary to regulate divergent loop contributions to the meson-meson scattering amplitudes in the strong-interaction sector. One finds lifetimes of (2.2±0.9)×10−18 s for the ground state of kaonium.